2011
DOI: 10.1007/s11033-011-1085-7
|View full text |Cite
|
Sign up to set email alerts
|

The mouse B cell-specific mb-1 gene encodes an immunoreceptor tyrosine-based activation motif (ITAM) protein that may be evolutionarily conserved in diverse species by purifying selection

Abstract: The B-lymphocyte accessory molecule Ig-alpha (Ig-α) is encoded by the mouse B cell-specific gene (mb-1), and along with the Ig-beta (Ig-β) molecule and a membrane bound immunoglobulin (mIg) makes up the B-cell receptor (BCR). Ig-α and Ig-β form a heterodimer structure that upon antigen binding and receptor clustering primarily initiates and controls BCR intracellular signaling via a phosphorylation cascade, ultimately triggering an effector response. The signaling capacity of Ig-α is contained within its immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The mb-1 is a B lymphocytes-speci c gene, which encodes the B cell accessory molecule Iga. We chose mb-1 promoter and beta-globin locus control region served as positive and negative controls for DNA demethylation in B cells, respectively [14,15]; kidney genomic DNA was used as a non-lymphoid control (Data not shown) [11]. Bisul te sequence showed that the Dm element exhibits high methylation levels in pre-B cells, with no signi cant difference observed in the expression of RAG2(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mb-1 is a B lymphocytes-speci c gene, which encodes the B cell accessory molecule Iga. We chose mb-1 promoter and beta-globin locus control region served as positive and negative controls for DNA demethylation in B cells, respectively [14,15]; kidney genomic DNA was used as a non-lymphoid control (Data not shown) [11]. Bisul te sequence showed that the Dm element exhibits high methylation levels in pre-B cells, with no signi cant difference observed in the expression of RAG2(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD79 is heterodimeric transmembrane protein that is associated with membrane immunoglobulin and expressed in B cell at early stages of its development until the last stage of maturation before differentiation to plasma cells [36]. It has also been found in biphenotypic leukemia cases of myeloid leukemia, where it was coexpressed with myeloid markers on bone marrow blast cells [37].…”
Section: A B C D Ementioning
confidence: 99%
“…CD79a (also known as Ig-α or mb-1) is an integral membrane protein that is highly conserved among many species [16]. It is expressed at the very early stages of B cell development [17], and expression of CD79a is maintained until the last stage of maturation before differentiation to plasma cells [18], [19].…”
Section: Introductionmentioning
confidence: 99%